When ghosts speak : understanding the world of earthbound spirits - Winkowski, Mary Ann (Grand Central Publishing, 2009)
"Mary Ann Winkowski is the mother of two. She lives in an Ohio suburb where she goes to church every Sunday. And she sees and talks to ghosts."--Back cover